A „Kiáltó szó" és az Erdélyi Néppárt megalakítása - Sipos, József (Közép-Európai Közlemények, 2009)
After the First World War, Transylvania was fully annexed to Romania. After the first shock the significant number of the Hungarian minority in Transylvania tried to organized itself economically and politically. Our paper analyzes one of these efforts presenting how Károly Kós and his friends founded a party called Erdélyi Néppárt (Transylvanian Party) in Bánffyhunyad on the 5th of June, 1921.